Solving traveling salesman problems using branch and bound methods - Mustafa, Mamat (2019)
The traveling salesman problem is a well known optimization problem. Optimal solutions to small instances can be found in reasonable time by linear programming. However, since the TSP is NP-hard, it will be very time consuming to solve larger instances with guaranteed optimality. Setting optimality aside, there's a bunch of algorithms offering comparably fast running time and still yielding near optimal solutions. Therefore, in this study we will examine the search for solving TSP problem using branch and bound methods.